DESIGN AND ANALYSIS OF 5 KW SAVONIUS ROTOR BLADE - WIDODO, WAHYONO SAPTO; HASOLOAN, HAERY IAN PIETER; YAAKOB, MOHD YUHAZRI (Global Engineers and Technologists Review, 2012)
This paper presents the design and analysis of the Savonius rotor blade to generate 5 kW power output. The relevant design parameters and theories were studied in this paper and used to determine related design geometry and requirements of the Savonius rotor blade. The Savonius rotor was designed with the rotor diameter of 3.5 m and the rotor height of 7 m. The 3D model of Savonius rotor blade was created by using SolidWorks software. Computational Fluid Dynamics (CFD) analysis and structural Finite Element Analysis (FEA) are presented in this paper. CFD analysis was performed to obtain the pressure difference between concave and convex region of the blade while FEA was done to obtain the structural response of the blade due to the wind load applied in term of stresses and its displacements.